Demographic, socio-economic, and health factors associated with use of health services among internal migrants in China: an analysis of data from a nationwide cross-sectional survey. (October 2016) - Lu, Liming; Zeng, Jingchun; Zeng, Zhi
Abstract: Background: In 2014, approximately 253 million Chinese migrants had left their hometowns and were working in cities. Inequalities in demographic, socioeconomic, and health status for migrants place them at increased risk of health problems and marginalised them in the use of health-care services. We aimed to identify the inequalities that limit the use of health services among internal migrants in China, and to provide a reference point for health policy. Methods: Data were collected from 23 505 participants aged 15 years or older, from the 2014 China Labor Force Dynamic Survey (a nationwide cross-sectional survey covering 29 provinces with a multi-stage cluster, and stratified, probability sampling strategy) conducted by Sun Yat-sen University. Logistic regression analyses were used to study the associations between demographic (age, sex, marital status, type of hukou (the mandatory system of household registration), and migration status), socioeconomic (annual income, education, and social class) and health status (self-perceived general health and several chronic illnesses) variables and the use of health services (clinic visits during the past 2 weeks and hospital admission during the past 12 months). Ethical approval was obtained from Sun Yat-sen University (Guangdong, China). Informed consent was obtained from all participants. Findings: 2141 migrants and 21 364 residents were included. 71 (3·3%) migrants and 1296 (6·1%) residents underwent hospital admission during the past 12 months (OR 0·53, 95% CI 0·42–0·68); however, rates of 2-week clinic visits did not differ between the groups. After controlling for other variables, patients with more insurance, lower self-perceived general health, and a higher number of chronic illnesses were more likely to have 2-week clinical visits (all p<0·0001) and hospital admission during the past 12 months (all p<0·0001) compared with patients with less insurance, higher self-perceived general health, and a lower number of chronic illnesses, respectively; people from disadvantaged classes were less likely to be hospitalised (OR 0·92, 95% CI 0·86–0·98) than those from advantaged classes. Interpretation: This study showed that there are inequalities in demographic, socioeconomic, and health status associated with the use of health services for migrants in China. Prudent health policy with equitable use of health services to eliminate these inequalities should be a priority in shaping China's health-care system reform. Funding: This study had no funding.